Identification of stress and coping strategies among primary school teachers at selected schools in Papar, Sabah - Aslinah binti Wasli (Kulliyyah of Education, International Islamic University Malaysia, 2018)
Stress leads to decreased motivation among teachers. It causes them to lose focus, lack clear goal, lose interest and lose the inner commitment. Teachers always face a dilemma of having to bear the burden of handling massive amount of work either at home or at school. Awareness of the need to manage stress has contributed to various studies which examine the levels of stress, causes and effects of stress and coping strategies. Thus, this study focuses on stress among primary school teachers. The purpose of this study is to investigate stress and coping strategies among teachers in primary schools at 10 selected schools in Papar, Sabah. Specifically, this study examines the level of stress among teachers as well as the combination of stress factors and the most common strategies used by teachers to cope their stress. The study employed a survey questionnaire comprised of 4 sections to collect the data. The sample consisted of 140 teachers from 10 rural schools in Papar, Sabah. Stratified and simple random sampling methods were used to select the sample. The data were analyzed using Statistical Package of Social Sciences (SPSS) Version 21 by using frequency, mean, percentage, multiple regression analysis (MRA), independent t-test and ANOVA. The findings revealed that primary school teachers experience a moderate level of stress. Workloads, time constraints and pupils behaviour were identified as major factors of stress. The most common strategies used by primary teachers to cope with stress include expecting that stress problem encountered can be resolved amicably, solving problems through religious approaches, performing favoured or preferred activities and expecting something good would happen after encountering difficulties. This study is expected to be a reference needed to identify the problem of stress among primary teachers in rural areas in order to find the best solution that teachers can apply in handling their multiple roles and as a contribution to body of knowledge. The future research should consider by making a comparison with teachers who teach Level 1 pupils (Standard 1 to Standard 3) who are learning literacy, numeracy and so on, with teachers who teach Level 2 (Standard 4 to Standard 6) which lead the UPSR exam preparation to identify their levels of stress.